Modelling and active vibration control for flexible beam - Sai, Seng Ohn. (2008)
This dissertation reports a study on modeling and control of a flexible beam. We use piezoelectric devices, which provide many attractive features such as light weight, high sensitivity and large bandwidth, as sensor and actuator. System identification is carried out by using frequency response method and then a mathematical model is derived and verified.